Malaria Illness Experiences and Health-Seeking Behaviours among In-school Adolescents in Ibadan North Local Government Area, South-west Nigeria (African Journal of Biomedical Research, 2023)
The burden of malaria among In-School Adolescents (ISAs) is enormous; yet, their malaria-related illness experiences and health-seeking behaviours have not been adequately explored. The study investigated malaria-related illness experiences and health seeking behaviours among ISA in Ibadan North Local Government Area (IBNLGA), Oyo State, Nigeria. The study was conducted in both private and public secondary schools located in IBNLGA, Oyo State, Nigeria. A descriptive cross-sectional design was adopted and a four-stage sampling technique was used to select 430 ISAs from 12 secondary schools. A self-administered questionnaire was used to collect data. Data were analyzed using descriptive statistics, chi-square test and logistic regression at p=0.05. Respondents’ age was 14.5±2.2 years and 82.7% were from public schools. Most (99.8%) respondents had ever-experienced malaria and 51.8% of them reportedly had malaria within the three months preceding the study. Majority (83.1%) claimed to own a mosquito net; however, only 48.5% use it daily. Treatment pathways adopted by respondents during malaria episodes included: visiting hospital to receive treatment (76.1%); using drugs purchased from patent medicine vendors (70.7%), and use of herbs (66.9%). Significant associations were noted between respondents’ sex, age and class and their health seeking behaviour with their respective p-values being 0.023, 0.001 and 0.013. Malaria is a common disease among the in-school adolescents; yet use of mosquito nets among them was not overwhelming. Furthermore, unreliable malaria treatment practices were common among them. Health education interventions including training and advocacy relating to consistent use of net and appropriate malaria-related health-seeking behaviours are recommended.